Disk diffusion susceptibility testing of the Bacteroides fragilis group. - Horn, R (1987)
The susceptibilities of 225 isolates of the Bacteroides fragilis group to six antibiotics were determined by a new disk diffusion test in Wilkins-Chalgren agar and by the standard agar dilution method. For disk diffusion, the bacteria were directly suspended in saline and immediately swabbed onto 15-cm agar plates. Disks of cefoxitin (30 micrograms), chloramphenicol (30 micrograms), clindamycin (2 micrograms), moxalactam (30 micrograms), imipenem (10 micrograms), and ticarcillin (75 micrograms) were applied, and the plates were incubated at 37 degrees C in an anaerobic atmosphere. Zone sizes were measured at 24 h. The results of disk diffusion and agar dilution were compared by regression analysis by the method of least squares and by the error rate-bounded method. Zones were easily measured for 216 strains (96%). The correlation between the MICs and diameters of inhibition for cefoxitin, clindamycin, moxalactam, and ticarcillin was generally good. A correlation could not be established for chloramphenicol and imipenem, as there were too few resistant strains. With the recommended resistance breakpoints, the following susceptible and resistant zone diameter breakpoints could be established: cefoxitin, less than or equal to 19 and greater than or equal to 21 mm; clindamycin, less than or equal to 14 and greater than or equal to 18 mm; moxalactam, less than or equal to 21 and greater than or equal to 25 mm; and ticarcillin, less than or equal to 15 and greater than or equal to 16 mm. By applying these zone criteria, the percentage of false-susceptible strains was less than 1% and of false-resistant strains was less than 4% for the drugs tested.